A Case Report of Primary Malignant Melanoma of the Gallbladder with Multiple Metastases - Steven H. Adams; Erinn Luo; Daniel Lozeau; Xiaoyun Wen (Case Reports in Pathology)
Primary malignant melanoma of the gallbladder is an extremely rare tumor with approximately 39 cases described in the literature so far. However, since the first case was reported in 1907, it remains controversial whether gallbladder involvement in malignant melanoma is primary or metastatic. Here, we report a case of primary malignant melanoma of the gallbladder. A 52-year-old male presented to the emergency department with right upper quadrant abdominal pain and was found to have tumefactive sludge filling the majority of the gallbladder with possible gallbladder wall thickening on ultrasonography. A laparoscopic cholecystectomy was performed for presumed acute cholecystitis. Histopathologic examination of the gallbladder revealed malignant melanoma arising from the mucosa of the gallbladder. Further clinical investigation excluded other primary sites, supporting a diagnosis of primary malignant melanoma of the gallbladder.